Cornelius Castoriadis. The Greek Imaginary: From Homer to Heraclitus. Edited by E. Escobar, M. Gondicas, and P. Vernay. Translated by J. V. Garner, and M.-C. Garrido Sierralta. Edinburgh: Edinburgh University Press, 2023. - Bifis, George Peter; Giannopoulou, Phaedra; Argyrakou, Angeliki-Maria (Conatus - Journal of Philosophy, 2023)
This essay will discuss the combined seminars presented in the book “The Greek Imaginary: from Homer to Heraclitus” by Cornelius Castoriadis. In these seminars he dissects Ancient Greek culture, politics, and religion in an investigative and analytic way. Through ancient Greek mythology and the Homeric texts a lot of information can be derived regarding the everyday lives, ideology, and philosophy of the time; all of the aforementioned will be explicated as well as the way Castoriadis specifically interprets certain aspects of ancient Greek life in his own unique way. Additionally, we will look into the language of the texts, the meaning of the French vocabulary that was used at the seminars and the ways in which it can be accurately translated in English.